العوامل الخمسة الكبرى للشخصية وعلاقتها بالرضا الزواجي لدى عينة من المتزوجات السعوديات بجدة: دراسة مقارنة - الشمرانى، فاطمة عبدالرحمن عبدالله; خليفة، هدى بنت عاصم محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2019)
هدفت الدراسة الحالية إلى الكشف عن الدور الذي تقوم به العوامل الخمسة الكبرى للشخصية وعلاقتها بالرضا الزواجي لدى المتزوجات السعوديات، ولتحقيق هذا الهدف تم استخدام المنهج الوصفي الارتباطي المقارن، تكونت عينة الدراسة من (200) من المتزوجات السعوديات بمدينة جدة، حيث تتراوح أعمارهم بين 17 إلى أكثر من 32 سنة وقد تم اختيار العينة بطريقة العينة المتاحة (المتيسرة). ولتحقيق أهداف الدراسة استخدمت الباحثة مقياس قائمة العوامل الخمسة الكبرى للشخصية من إعداد "هشام الحسيني" ومقياس "الرضا الزواجي" من إعداد (walter w.hudson, 1982)، ولتحليل النتائج استخدمت الباحثة الأساليب الإحصائية التالية: التكرارات والنسب المئوية، المتوسط الحسابي، الانحراف المعياري، معامل ألفا كرونباخ، معامل التجزئة النصفية، معامل ارتباط بيرسون، اختبار (T) لعينتين مستقلتين، اختبار تحليل التباين، اختبار تحليل الانحدار التدريجي وكانت أهم نتائج الدراسة: توجد علاقة سالبة بين الرضا الزواجي (الأبعاد والدرجة الكلية) وبين بعد العصابية كما توجد علاقة موجبة بين الرضا الزواجي (الأبعاد والدرجة الكلية) وبين الانبساط- الصفاوة- الطيبة- يقظة الضمير، كما يوجد فروق بين الرضا الزواجي نتيجة لاختلاف مدة الزواج، بينما لا توجد فروق ذات دلالة إحصائية بين مرتفعي ومنخفضي الرضا الزواجي وسمة الانبساط لدى عينة البحث.
This study aimed at revealing the role of five main factors in personality and its relation to marital satisfaction among Saudi women married. To achieve this goal, the researcher used the descriptive analytical approach. The study sample consisted of 200 Saudi women married in Jeddah, aged between 17 and over 32 years. In order to achieve the objectives of the study, the researcher used a list of the five main factors to measure the personality prepared by Hisham al-Husseini and its researcher and the measure of "marital satisfaction" by Walter H. Hudson. 1982 To analyze the results, the researcher adopted the following statistical methods: The mean, standard deviation, alpha cronbach, split half reliability, Pearson correlation coefficient, T test for two independent samples, variance analysis test and linear regression analysis. The main results of the study were: There is a negative relationship between marital satisfaction (dimensions and total degree) and the nervous dimension in the sample of the study. There is a positive relationship between marital satisfaction (dimensions and total degree) and purity - purity. There are statistically significant differences between marital satisfaction due to differences in duration of marriage. There were no statistically significant differences between high and low marital satisfaction and degree of extinction in the study sample.
Keywords: الرضا الزواجى -- السعودية -- العلاقات الإنسانية